Proterozoic paleocurrents and depositional history of the East Arm fold belt, Great Slave Lake, Northwest Territories - Hoffman, Paul (Canadian Journal of Earth Sciences, 1969)
Nearly 40 000 ft (~12 190 m) of unmetamorphosed Aphebian (and possibly lowermost Helikian) sedimentary and volcanic rocks are exposed in the East Arm of Great Slave Lake. This sequence is an erosional remnant of an Appalachian-type geosynclinal complex with a NNW depositional strike. Integrated paleocurrent, stratigraphic, and sedimentological analysis reveals three stages in the depositional history of the complex: (1) a double transgressive, pre-orogenic miogeosyncline, which received sediment from a distant cratonic source to the ENE and which becomes thicker and more eugeosynclinal to the WSW; (2) a regressive, syn-orogenic exogeosyncline (clastic wedge), which received sediment from rapidly uplifted tectonic lands to the WSW; and (3) a continental, post-orogenic taphrogeosyncline (down-faulted intermontaine trough), which received sediment locally from block-fault scarps within the East Arm area.Facies predictions based on this model provide criteria for establishing stratigraphic correlation and contiguity between the East Arm and other Aphebian sequences in the northwestern Canadian Shield. The prevailing depositional strike is roughly perpendicular to the tectonic strike of the East Arm Fold Belt, and it should not therefore be assumed that depositional strike parallels tectonic strike in other belts. The Bear Province may have been the site of the orogenically active axial zone of the geosyncline, but that part of the Churchill Province near the East Arm remained passive until the final post-orogenic stage of sedimentation and may therefore be of epeirogenic origin.